Building Computer Vision Projects with OpenCV 4 and C : Implement complex computer vision algorithms and explore deep learning and face detection /: Implement complex computer vision algorithms and explore deep learning and face detection. (2019) - Millán Escrivá, David; Joshi, Prateek; G. Mendonça, Vinícius; Shilkrot, Roy
No abstract available